Possible future evolutionary consequences to Homo as a result of the implementation of biotechnology - Saniotis, Arthur; Galassi, Francesco M.; Henneberg, Maciej (Anthropological Review, 2024)
Biotechnology has become one of the most powerful forces on the planet, since it is capable of altering life processes at a molecular level. Since human bodies are dynamic biological systems, medicine requires to understand the evolutionary antecedents of Homo, especially in relation to neurohormonal regulation. Furthermore, increasing human dependence on biotechnology has led to relaxed natural selection in Homo, with subsequent increase of genetic load. In this paper, we speculate on the possible consequences of the application of parsimoniously derived biotechnologies onto the biological system of humans, with special attention to three areas: 1. human brain augmentation; 2. biotechnology and public health; 3. relaxed natural selection and genetic load. Human ability to manipulate and alter the structure and function of the body may not only make natural selection redundant but will be guided by a teleology whose purpose will seek to improve upon nature’s design.